Autonomic function based on heart rate variability in children with laryngopharyngeal reflux - Yunizaf, Rahmanofa; Restuti, Ratna Dwi; Rachmawati, Elvie Zulka Autzia; Putranto, Rudi; Kusumayati, Agustin; Hegar, Badriul (Paediatrica Indonesiana, 2025)
Background The pathophysiology of laryngopharyngeal reflux (LPR) is yet to be completely understood, but autonomic dysregulation may have a role in the opening of esophageal sphincters controlled by the parasympathetic nervous system, especially the vagal nerve. Autonomic dysregulation can be detected through heart rate variability (HRV). Currently, studies that identify autonomic nerve dysfunction through HRV in LPR patients are few, especially in the pediatric population. Objective To identify autonomic nerve dysfunction  in pediatric LPR patients with HRV components. Method This study involved 74 pediatric patients, 35 with LPR and 39 without LPR, from  Dr. Cipto Mangunkusumo Hospital, Jakarta, from September 2023 to April 2024. Diagnostics for LPR included endoscopy and Reflux Symptom and Sign Instrument (RSSI) scoring, while measurement of autonomic nerve dysfunction was determined by HRV. The HRV was evaluated by standard deviation normal to normal (SDNN) assessment of the heart’s interbeat interval (IBI) and low frequency/high frequency ratio (LF/HF). Results  Neither HRV measurement, SDNN or LF/HF, were significantly associated with autonomic nerve dysfunction in pediatric patients with LPR. Conclusion Autonomic nerve dysfunction measured by HRV was not associated with LPR in pediatric patients.